Health Care at Risk : a Critique of the Consumer-Driven Movement - Jost, Timothy S. (e-Duke books scholarly collection., 2007)
In Health Care at Risk Timothy Stoltzfus Jost weighs in on consumer-driven health care (CDHC), which many policymakers and analysts are promoting as the answer to the severe access, cost and quality problems afflicting the American health care system.